Prompt isothermal decay of thermoluminescence in MgB4O7:Dy, Na and LiB4O7:Cu, In dosimeters. (January 2016) - Kitis, G.; Polymeris, G.S.; Sfampa, I.K.; Prokic, M.; Meriç, N.; Pagonis, V.
Abstract: According to standard delocalized kinetic models of thermoluminescence (TL), when an irradiated sample is held at a high temperature T, the isothermal TL signal will decay with a characteristic thermal decay constant λ which depends strongly on the temperature T . This prediction of standard delocalized kinetic theory is investigated in this paper by studying two TL dosimeters, MgB4 O7 :Dy, Na and LiB4 O7 :Cu, In (hereafter MBO and LBO correspondingly). In the case of LBO it was found that the thermal decay constant λ of the main dosimetric TL peak follows exactly the predictions of standard delocalized kinetic theory. Furthermore, the thermal activation energy of the main peak evaluated by the isothermal decay method is in full agreement with values obtained from initial rise and glow curve fitting methods. However, in the case of MBO it was found that the thermal decay constant λ varies little with the isothermal decay temperature T . In order to explain these unusual results for MBO, the TL glow curves and isothermal decay curves were analyzed using analytical expressions derived recently from a radiative tunneling recombination model. Based on the different behavior of the two TL dosimeters, it is suggested that the isothermal decay of TL at high temperatures can be used to discriminate between radiative delocalized recombination and radiative localized recombination processes. Highlights: Isothermal decay of TL in MgB4 O7 :Dy, Na and LiB4 O7 :Cu, In is studied. The TL of LiB4 O7 :Cu, In is due to delocalized transitions. The TL of MgB4 O7 :Dy, Na is due to tunneling transitions. Recent TL expressions for delocalized and localized transitions are used to explain the results.